Microstrain distributions in polycrystalline thin films measured by X‐ray microdiffraction. Issue 2 (18th March 2016) - Schäfer, N.; Chahine, G. A.; Wilkinson, A. J.; Schmid, T.; Rissom, T.; Schülli, T. U.; Abou-Ras, D.
Abstract : X‐ray microdiffraction is used for acquiring microstrain distribution maps in polycrystalline thin films. Abstract : Microstrain distributions were acquired in functional thin films by high‐resolution X‐ray microdiffraction measurements, using polycrystalline CuInSe2 thin films as a model system. This technique not only provides spatial resolutions at the submicrometre scale but also allows for analysis of thin films buried within a complete solar‐cell stack. The microstrain values within individual CuInSe2 grains were determined to be of the order of 10 −4 . These values confirmed corresponding microstrain distribution maps obtained on the same CuInSe2 layer by electron backscatter diffraction and Raman microspectroscopy.